2020
DOI: 10.1515/med-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise and cardiac remodeling in a myocardial infarction model

Abstract: AbstractWe investigated the effects of voluntary exercise after myocardial infarction (MI) on cardiac function, remodeling, and inflammation. Male C57BL/6J mice were divided into the following four groups: sedentary + sham (Sed-Sh), sedentary + MI (Sed-MI), exercise + sham (Ex-Sh), and exercise + MI (Ex-MI). MI induction was performed by ligation of the left coronary artery. Exercise consisting of voluntary wheel running started after the operation and continued for 4 weeks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As with the forced exercise models discussed above, wheel running reliably induces physiological cardiovascular adaptations including a reduction in resting HR 107 and physiological hypertrophy, as well as protective 108 and therapeutic 109 effects (Table 3). 107,167,169,172 Early bioinformatic analyses revealed enrichment of cell cycle pathways in exercised hearts after forced swimming, and multiple markers of proliferation were increased in cardiomyocytes from exercised hearts.…”
Section: Animal Models Of Exercise Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…As with the forced exercise models discussed above, wheel running reliably induces physiological cardiovascular adaptations including a reduction in resting HR 107 and physiological hypertrophy, as well as protective 108 and therapeutic 109 effects (Table 3). 107,167,169,172 Early bioinformatic analyses revealed enrichment of cell cycle pathways in exercised hearts after forced swimming, and multiple markers of proliferation were increased in cardiomyocytes from exercised hearts.…”
Section: Animal Models Of Exercise Conditioningmentioning
confidence: 99%
“…Generally low intensity but distances run are generally longer than with involuntary models; intensity can be increased with weighted wheels 106 2 107 -8 107 wk Increased FS, 51 increased LV mass, 107 increased cardiomyocyte size, increased capillary density, 51 physiological transcriptional profile (eg, decreased β/αMHC ratio), 51 cardiomyogenesis, 51 protective 108 and therapeutic 109 effects in pathological models TAC NA NA NA cardiac hypertrophy: 1-2 wk; heart failure: 6-8 wk 37,110 Reduced FS, increased LV mass, increased fibrosis, 37 decreased SERCA2a expression and activity, 41,42 pathological transcriptional profile (increased β/αMHC ratio, ANP, BNP expression, decreased PGC-1α transcript expression) 50 Consistent with this, cardiomyocyte-specific deletion of CITED4 impaired cardiac adaptation to both physiological and pathological stimuli, culminating in worse heart failure, fibrosis, and apoptosis after pressure overload. 119 Other examples of molecular transducers of exercise phenotypes discovered in the swimming model include the miRs miR-17-3p 120 and miR-222, 6 and the long noncoding RNA cardiac physiological hypertrophy-associated regulator, 82 all of which increase in exercised hearts and appear to contribute to cardiomyocyte growth and possibly proliferation.…”
Section: Voluntary Bouts Bout Durations Varymentioning
confidence: 99%
“…In addition, Zhang et al showed that changes in left ventricular remodeling were more significant when exercise training programs were initiated in the acute phase after MI. According to the 2020 ESC Guidelines on sports cardiology and exercise in patients with cardiovascular disease, patients should be referred to an early exercise training program for 8–12 weeks after an acute coronary syndrome (ACS) in order to reduce cardiac mortality and rehospitalization [ 120 , 121 , 122 ].…”
Section: Therapeutic Implications In Adverse Cardiac Remodelingmentioning
confidence: 99%